1986
DOI: 10.1126/science.2425430
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a New Human Retrovirus from West African Patients with AIDS

Abstract: The etiological agent of AIDS, LAV/HTLV-III, is common in Central Africa but is not endemic in other areas of that continent. A novel human retrovirus, distinct from LAV/HTLV-III, has now been isolated from two AIDS patients from West Africa. Partial characterization of this virus revealed that it has biological and morphological properties very similar to LAV but that it differs in some of its antigenic components. Although the core antigens may share some common epitopes, the West African AIDS retrovirus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
396
1
25

Year Published

1987
1987
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,075 publications
(425 citation statements)
references
References 27 publications
3
396
1
25
Order By: Relevance
“…Amino Viruses. Laboratory strains HIV-1(LAI) (2), HIV-1(NDK) (34), and HIV-2(ROD) (8) were produced in CEM cells. Macrophage-tropic HIV-1(89.6) (9) was produced in CEMx174 cells as previously described (35).…”
Section: Methodsmentioning
confidence: 99%
“…Amino Viruses. Laboratory strains HIV-1(LAI) (2), HIV-1(NDK) (34), and HIV-2(ROD) (8) were produced in CEM cells. Macrophage-tropic HIV-1(89.6) (9) was produced in CEMx174 cells as previously described (35).…”
Section: Methodsmentioning
confidence: 99%
“…Human immunodeficiency viruses type 1 and 2 represent a distinct group of lentiviruses associated with acquired immunodeficiency syndrome (AIDS) [1,2], An important characteristic of HIV-1 and HIV-2 is their high genomic diversity 1" [3][4][5]. It has been suggested that much of this genetic heterogeneity stems from the low fidelity of the reverse transcription step [6].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, the predominant virus is HIV-1, and generally when people refer to HIV without specifying the type of virus they will be referring to HIV-1. The relatively uncommon HIV-2 type is concentrated in West Africa and is rarely found elsewhere [8].…”
Section: Types Groups and Sub-types Of Hivmentioning
confidence: 99%